Inhibition of the photochromic behaviour of a 3, 3-diphenyl-3H-pyrano[3, 2-f]quinoline ligand by coordination to Ag(I) ions. (April 2020) - Edgar, Ross J.L.; Elliott, Paul I.P.; Fennessy, Rebecca V.; Gabbutt, Christopher D.; Heron, B. Mark; Pope, Simon J.A.; Sinopoli, Alessandro; Rice, Craig R.
Abstract: The synthesis and characterisation of a photoresponsive 3, 3-diphenyl-3 H -pyrano[3, 2- f ]quinoline ligand which contains both quinoline and thiazole N-donor moieties is described. This ligand acts as a bidentate N-donor ligand and the solid-state structure of a Ag(I) complex is reported. Whereas the free ligand exhibits typical photochromic behaviour, coordination with Ag(I) results in complete inhibition of the photochromic response. However, excitation wavelength dependent emission spectra demonstrated an increase in fluorescence response of the new Ag(I) complex. Graphical abstract: Image 1 Highlights: A new photochromic pyran centred ligand (L 1 ) has been efficiently synthesised. L 1, forms a complex, [L 1 Ag(H2 O)], with Ag(I) ions and the structure has been elucidated by X-ray crystallography. Complexation of L 1 with Ag(I) results in the complete inhibition of photochromism but generates a weak emission.